Effect of the infection of the mugilid fish Planiliza subviridis with the copepod Ergasilus rostralis: A haematological study - Al-Daraji, Salem; Mhaisen, Furhan (Journal of Biological Studies, 2023)
A total of 83 specimens of Planiliza subviridis were collected from Khor Al-Zubair lagoon, northwest Arab Gulf, Iraq. These fishes were found infected with the copepod Ergasilus rostralis Ho, Javarajan & Radhakrishnan, 1992. Blood parameters: total leukocyte count (WBCs), total red blood cells (RBCs), haemoglobin content (Hb%) and haematocrit volume (PCV) were investigated for lightly (1-5 parasites/fish), mildly (6-10 parasites/fish) and heavily (> 10 parasites/fish) infected fish groups in comparison with uninfected fishes. Uninfected fishes had the highest values of all blood parameters, except WBCs. Hb%, PCV and RBCs significantly decreased in all infected groups when compared with the uninfected group. WBCs significantly increased in all infected fish groups in comparison with the uninfected fishes. WBCs insignificantly decreased in heavily infected group when compared with mildly infected fishes.